Advances of polymer binders for silicon‐based anodes in high energy density lithium‐ion batteries. Issue 5 (30th March 2021) - Zhao, Yu‐Ming; Yue, Feng‐Shu; Li, Shi‐Cheng; Zhang, Yu; Tian, Zhong‐Rong; Xu, Quan; Xin, Sen; Guo, Yu‐Guo
Abstract: Conventional lithium‐ion batteries (LIBs) with graphite anodes are approaching their theoretical limitations in energy density. Replacing the conventional graphite anodes with high‐capacity Si‐based anodes represents one of the most promising strategies to greatly boost the energy density of LIBs. However, the inherent huge volume expansion of Si‐based materials after lithiation and the resulting series of intractable problems, such as unstable solid electrolyte interphase layer, cracking of electrode, and especially the rapid capacity degradation of cells, severely restrict the practical application of Si‐based anodes. Over the past decade, numerous reports have demonstrated that polymer binders play a critical role in alleviating the volume expansion and maintaining the integrity and stable cycling of Si‐based anodes. In this review, the state‐of‐the‐art designing of polymer binders for Si‐based anodes have been systematically summarized based on their structures, including the linear, branched, crosslinked, and conjugated conductive polymer binders. Especially, the comprehensive designing of multifunctional polymer binders, by a combination of multiple structures, interactions, crosslinking chemistries, ionic or electronic conductivities, soft and hard segments, and so forth, would be promising to promote the practical application of Si‐based anodes. Finally, a perspective on the rational design of practical polymer binders for the large‐scale application of Si‐based anodes is presented. Abstract : Polymer binders play a crucial role in alleviating the volume expansion and maintaining the integrity and stable cycling of Si‐based anodes. This review presents the state‐of‐the‐art designing of polymer binders for Si‐based anodes based on the linear, branched, crosslinked, conjugated polymer structures. Besides, the multifunctional design of polymer binders for the practical application of Si‐based anodes has been discussed.